Environmental passives of the hydrocarbon subsector and impacted sites: an analysis of their current situation and perspective - Bazán-Suárez, Daimer E. (2024)
The exploitation of hydrocarbons in Peru began in 1863, in a context in which environmental regulation was nonexistent; As a consequence, the generation of environmental passives derived from this activity was abundant. Objective. Analyze the current situation regarding the management of the environmental passives of the hydrocarbon subsector (after this, PASH) and impacted sites (after this, SIM) in Peru. Methodology. It involved the analysis of documentary information, largely sent by the Environmental Assessment and Supervision Agency (OEFA) and the Ministry of Energy and Mines (MINEM), through access to public information. Results. The management of the PASH and the SIM in Peru are still in the initial stage, with identification actions presenting the greatest progress regarding the determination of those responsible and the approbation of abandonment plans and rehabilitation plans. Conclusions. In the posterior greater efforts will be required to achieve an adequate environmental sanitation of these spaces; which would be tightly linked to the commitment and the effectiveness with which each of the institutions involved perform.